Neoadjuvant Chemotherapy or Endocrine Therapy for Invasive Ductal Carcinoma of the Breast With High Hormone Receptor Positivity and Human Epidermal Growth Factor Receptor 2 Negativity - Zhang, Jiaqiang (JAMA Netw Open, 2021)
IMPORTANCE: Although neoadjuvant endocrine therapy (NET) is an alternative to chemotherapy for strongly hormone receptor (HR)–positive and human epidermal growth factor receptor 2 (ERBB2)–negative breast cancer, evidence is currently lacking regarding the probable survival outcomes of NET in comparison with those of neoadjuvant chemotherapy (NACT) for this cancer. OBJECTIVE: To evaluate all-cause mortality among patients with strongly HR-positive and ERBB2-negative breast cancer treated with NET vs NACT. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included patients with a diagnosis of invasive ductal carcinoma (IDC) with strong HR positivity and ERBB2 negativity, treated between January 1, 2009, and December 31, 2016, with follow-up from the index date (ie, date of IDC diagnosis) to December 31, 2018. The data came from the Taiwan Cancer Registry Database. Data were analyzed from January to November 2020. EXPOSURES: NET vs NACT for IDC with strong HR positivity and ERBB2 negativity. MAIN OUTCOMES AND MEASURES: The primary end point was all-cause mortality. Propensity score matching was performed, and Cox proportional hazard models were used to analyze all-cause mortality among patients undergoing different neoadjuvant treatments. RESULTS: A total of 640 patients (297 [46.4%] aged 20-49 years) undergoing NET (145 patients [22.7%]) or NACT (495 patients [77.3%]) were eligible for further analysis. In the multivariate Cox regression analyses, the adjusted hazard ratio (aHR) for all-cause mortality among the NET cohort compared with the NACT cohort was 2.67 (95% CI, 1.95-3.51; P < .001). The aHRs for age were 1.13 (95% CI, 1.03-2.24), 1.25 (95% CI, 1.13-2.45), and 1.37 (95% CI, 1.17-3.49) for all-cause mortality among patients aged 50 to 59, 60 to 69, and 70 years or older, respectively, compared with those aged 20 to 49 years (P = .002); the aHR for all-cause mortality among premenopausal women was 1.35 (95% CI, 1.13-1.56) compared with postmenopausal women (P < .001); and that of patients with a Charlson Comorbidity Index score of 2 or greater was 1.77 (1.37-2.26) compared with those with a score of 0 (P < .001). The aHRs of all-cause mortality for clinical tumor stage 2, 3, and 4 compared with 1 were 1.84 (95% CI, 1.07-3.40), 1.97 (95% CI, 1.03-3.77), and 2.49 (95% CI, 1.29-4.81), respectively (P = .009). The aHRs for all-cause mortality by clinical nodal (cN) stages were 1.49 (95% CI, 1.13-1.99) and 1.84 (95% CI, 1.31-2.61) for cN stage 1 and cN stages 2 or 3, respectively, compared with cN stage 0 (P = .005); those for differentiation were 1.77 (95% CI, 1.24-2.54) and 2.31 (95% CI, 1.61-3.34) for differentiation grade 2 and differentiation grade 3, respectively, compared with differentiation grade 1 (P < .001). CONCLUSIONS AND RELEVANCE: The findings of this study suggest that for patients with strongly HR-positive and ERBB2–negative IDC, NACT may be considered the first choice for neoadjuvant treatment.